2006
DOI: 10.1186/1471-2229-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The effective functional analysis of male gametophyte development requires new tools enabling the spatially and temporally controlled expression of both marker genes and modified genes of interest. In particular, promoters driving expression at earlier developmental stages including microspores are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Both VvWRKY13 , 59 and 57 , belonging to Group I, were higly expressed in stamen and pollen tissues and are closely related to Arabidopsis AtWRKY34 , which was shown to have a role in coordinating gene expression during the formation of the tapetum and microspores. 82 …”
Section: Discussionmentioning
confidence: 99%
“…Both VvWRKY13 , 59 and 57 , belonging to Group I, were higly expressed in stamen and pollen tissues and are closely related to Arabidopsis AtWRKY34 , which was shown to have a role in coordinating gene expression during the formation of the tapetum and microspores. 82 …”
Section: Discussionmentioning
confidence: 99%
“…Like pAt5g17340:UidA:GFP, there are other marker lines that use Arabidopsis promoters to induce convincing GUS staining in all the male gametophytic stages (Honys et al 2006), yet the reported staining intensity in their uninucleate microspores is not as strong as in the pAt5g17340:UidA:GFP marker line.…”
Section: Discussionmentioning
confidence: 99%
“…Several Arabidopsis promoter sequences have also been shown to induce strong GUS staining in Arabidopsis flowers, in a male gametophyte and anther specific manner. However, these Arabidopsis promoters, either do not induce GUS staining in all stages of the male gametophyte, or if they do, they do not exhibit strong GUS staining at some of these stages (in particular in uninucleate microspores) (Moore et al 1997; Li et al 1998; Honys et al 2006; Takeda et al 2006; Gibalová et al 2009; Phan et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The BP clones pDONR-P4-P1R- pLAT52 and pDONR-P2R-P3-mRFP were kindly provided by Prof. David Twell (Leicester University, UK) (Eady et al, 1994). MSP1 promoter was cloned into pDONR-P4-P1R as described previously (Honys et al, 2006). WT plants were transformed via floral dip (Clough & Bent, 1998), and T2 or T3 plants homozygous for the transgene were used in this study.…”
Section: Methodsmentioning
confidence: 99%